Calcium dependent host innate immune resistance to influenza A virus infection - Goulding, Leah V. (2019)
Influenza A virus infection is a major threat to public health, claiming over half a million lives globally each year. Strategies to combat influenza virus infection include vaccination and antiviral therapy. Influenza virus vaccine escape mutants, arising from mutations resulting in antigenic alterations of their surface glycoproteins so they are no longer recognised by the host immune system, can limit the effectiveness of vaccines. Secondly, antivirals that directly target the virus inevitably apply selection pressure on the virus and lead to drug resistance. The onset of resistance has been documented for the neuraminidase inhibitors, currently the only class of anti-influenza drugs recommended by the World Health Organisation.